A Look at "From a Hypothesis" Syllogism from Aristotle to Farabi - Amin Shahverdi (Pizhūhish/hā-yi Falsafī- Kalāmī, 2018)
Although Aristotle had promised a detailed explanation of "from a hypothesis" syllogisms in Prior Analytics, he did not deliver this promise in any of his surviving works. After Aristotle, his students and followers introduced various types of this argument with respect to his book, Dialectics. In Alexander's explanation of Aristotle's Priori Analytics, he purposefully tries to include stoic indemonstrability in Aristotle's "from a hypothesis" syllogism and thus provide a framework for Aristotelian propositional logic. Alexander's efforts were implicitly accepted by various Peripatetic philosophers in later periods. Although Farabi, who takes inspiration from the Peripatetic school, understood Aristotle's "from a hypothesis" syllogism in the Peripatetic outline, he stayed true to some of Aristotle's teachings regarding this syllogism, particularly the condition of agreement in arguments and applied the term "hypothetical syllogism" to three different meanings without any particular indication. However, Farabi's understanding of conditional syllogisms as being one of the types of "from a hypothesis" syllogisms seems to be more similar to Galen's view than to Alexander's.